Positional variation of applicators during low dose rate intracavitary brachytherapy for cervical cancer: a prospective study - Koushik, Kirthi; Bilimagga, Ramesh; Rao, Nirmala; Janaki, M G; Ponni, Arul; Rajeev, A G (Journal of contemporary brachytherapy, 2010)
In order to know the effect of variation in position of applicators to the dose received by the tumor volume, critical organs such as rectum and bladder and the correlation of variation on the clinical outcome. 36 patients with histologically proven cervical cancer, undergoing intracavitary brachytherapy (ICBT) from October 2005 to December 2006 were the subjects of the study. Two pairs of orthogonal X-ray films were taken: one prior to loading of sources and the other after removal of sources. These patients were followed up as per the RTOG criteria. The median duration of insertion was 25 hours with a median follow up period of 6.7 months. The translational variation of the applicator position for all patients was 3 mm and 1 mm (2 SD), respectively, in the patient's lateral and antero-posterior direction. The rotational variation was 3 and 4 degrees (2 SD) in the patient's transverse and sagittal planes. Detailed analysis of source movement showed following changes in median dose: point A: 14%, point B: 2%, point P: 1%, Rectum 1: 3.5%, Rectum 2: 4% and Bladder: 9.1%. The incidence of rectal toxicity was 6/36 (16.7%) and that of bladder was 1/36 (2.8%). When the variables were grouped to evaluate the relationship, our study showed statistically significant relationship between: R2 and rectal toxicity ( value: 0.002), point A and rectal toxicity (Pearson: 0.792), lateral displacement/anteroposterior displacement and rectal toxicity ( value: 0.012/0.003), beta angle and R2 ( value: 0.002). The geometric relationships between the ICBT applicators and the critical structures vary during the course of low dose rate brachytherapy. Source movement does result in significant dose alterations in terms of increased rate of complications, but its impact on cure rates needs to be studied in the future.